To find the midpoint of the points (2, -2) and (6, 5), you can average the x-coordinates and the y-coordinates of the two points. The formula for the midpoint \((M)\) between two points \((x_1, y_1)\) and \((x_2, y_2)\) is given by:
\[ M = \left(\frac{x_1 + x_2}{2}, \frac{y_1 + y_2}{2}\right) \]
In this case:
- \(x_1 = 2\)
- \(x_2 = 6\)
- \(y_1 = -2\)
- \(y_2 = 5\)
To find the x-coordinate of the midpoint:
\[ \frac{6 + 2}{2} = \frac{8}{2} = 4 \]
To find the y-coordinate of the midpoint:
\[ \frac{5 + (-2)}{2} = \frac{5 - 2}{2} = \frac{3}{2} = 1.5 \]
So, the midpoint is \( (4, 1.5) \).
Now, regarding your question about "adding 6 + 2 then dividing by 2":
- This calculation finds the average of the x-coordinates, \( 6 \) and \( 2 \), giving the x-coordinate of the midpoint.
Therefore, the correct answer is:
It finds the average distance between the two x-values of the points.